Karakteristik Organoleptik Dendeng Batokok dengan Bahan Pengasap dan Lama Pengasapan yang Berbeda - Jaya Putra Jahidin (Fakultas Peternakan Universitas Jambi, 2012)
The objectiveof this study was to studythe characteristics of dendeng batokok that made with different duration of fumigationand the use of coconut shell, medang sawdust and rice husk as smoke material. Smokedduration was conducted during each 30, 60 and 90 minutes. Parameters observed during research were organoleptic attributes (colour, texture, aroma and taste). Theexperimental design used complete randomized design (CRD) with three replications. Nonparametric data of organoleptic tests processed statistically by Kruskal-Wallis method. Data processing using the program Minitab 15 version. The results ofthis study indicatethat; 1) the selected of dendeng batokok with the highest average value is 60 minutes for coconut shell smoking during, 90 minutes for medang sawdust smoking medang and 90 minutes for rice husk smoking, (2) the use of beef and buffalo meat with smoking coconut shell, medang sawdust and rice husk showed no real difference on organoleptic characteristics.